Das erweiterte Museum Medien, Technologien und Internet - Franken-Wendelstorf, Regina; Greisinger, Sybille; Gries, Christian (MuseumsBausteine, 2019)
Today, museums use various media to convey and communicate content. The spectrum ranges from print media to multimedia productions, hands-on and media stations to interactive, software and web-based offers. These change the "learning location museum" and expand it into digital space. This volume documents current concepts and technologies. It illuminates important instruments such as websites, online collections, social media, media stations, multimedia guides and essential topics such as e-learning, e-publishing, storytelling or digital strategies. In addition, concrete tips and recommendations for action regarding the conception, production and operation of media in the museum are given. An e-book and a digital toolkit with constantly updated material as well as media and application examples complete the publication.